KETAHANAN NASIONAL SEBAGAI KEKUATAN PENANGKALAN: SATU TINJAUAN DARI SUDUT KEPENTINGAN HANKAM - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
From the defence-security point of view, national resilience serves to ward off threats to stability. With the end of the cold war, the military threat from abroad has almost disappeared, but non-physical challenges from the globalization of information have increased. Legally there is still national sovereignity, but in practice the dynamics of our society develops in interaction with other nations. So we must constantly update our perception of our environment, as well as the new paradigms within our own life. Failure to adapt to these new paradigms --openness, for example-- can have grave consequences on stability. New information raises new hopes